2009
DOI: 10.1111/j.1439-0531.2008.01113.x
|View full text |Cite
|
Sign up to set email alerts
|

Spermatozoa Characteristics in Six Psittacine Species Using Light Microscopy

Abstract: Even though breeding of companion birds has increased continuously for years, the fecundity assessment of birds has hardly been acknowledged. Knowledge of the structure of spermatozoa is crucial for evaluation of the basic reproductive biology of any species as well as for phylogenetic research and cladistic analyses of internal relationships. Spermatozoa of six different psittacine species (Nymphicus hollandicus, Myiopsitta monachus, Agapornis roseicollis, Melopsittacus undulatus, Tanygnathus lucionensis, Gua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…The fact that the majority of morphological abnormalities (50.2%) are located in the head region corresponds to findings in other avian species, such as passerines [Lüpold et al, 2009], emus [du Plessis andSoley, 2011], penguins [Waldoch et al, 2012], and psittacines [Stelzer et al, 2005[Stelzer et al, , 2009. The mean rate of 26.5% (range 6.0-55.0%) morphologically normal spermatozoa was low compared to 42-65% normal spermatozoa in three conure species (Aratinga acuticaudata, A. solsttialis, Guarouba guarouba) and 95% in blue-napped parrots [Stelzer et al, 2005].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The fact that the majority of morphological abnormalities (50.2%) are located in the head region corresponds to findings in other avian species, such as passerines [Lüpold et al, 2009], emus [du Plessis andSoley, 2011], penguins [Waldoch et al, 2012], and psittacines [Stelzer et al, 2005[Stelzer et al, , 2009. The mean rate of 26.5% (range 6.0-55.0%) morphologically normal spermatozoa was low compared to 42-65% normal spermatozoa in three conure species (Aratinga acuticaudata, A. solsttialis, Guarouba guarouba) and 95% in blue-napped parrots [Stelzer et al, 2005].…”
Section: Discussionsupporting
confidence: 80%
“…Semen donors might be evaluated and selected according to results of semen analysis offering better breeding options [Neumann et al, ]; semen collection and artificial insemination (AI) have been used in domestic fowl [Burrows and Quinn, ] and in falconry [Temple, ] for decades and have been described as useful tools in the conservation of rare avian species [Blanco et al, ; DOC, ; Waldoch et al, ]. In psittacines, semen collection via massage method and semen analysis have been performed in smaller species [Samour et al, ; Anderson et al, ; Samour, ; Stelzer et al, , ; Neumann et al, ], but rarely reported in larger parrots [Brock, ; DellaVolpe et al, ], and with only moderate success rates. The application of a recently developed apparatus for electro‐stimulated semen collection enabled the collection of semen samples from 109 psittacine species, including the Spix's macaw [Lierz et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…Using eosin blue, the differentiation of dead from alive sperm was effectively possible, as reported from viability analysis in other avian species (Behncke, 2002;Fischer, Neumann, Purchase, et al, 2014;Lierz et al, 2013;Neumann et al, 2013;Schneider et al, 2018Schneider et al, , 2019Stelzer et al, 2005Stelzer et al, , 2009 (Schneider et al, 2017(Schneider et al, , 2018.…”
Section: Discussionmentioning
confidence: 98%
“…For this reason, we intended the evaluation of conventional live/dead stains in the first part of the study and the comparison with a modern fluorescence dye in the second part of the study; both backed up by a correlation with sperm motility results of the same samples. In particular, eosin blue, a single colorimetric stain that has been successfully used in sharp-tailed grouse (Schneider et al, 2019) and various psittacine species (Behncke, 2002;Fischer, Neumann, Purchase, et al, 2014;Lierz et al, 2013;Schneider et al, 2017Schneider et al, , 2018Stelzer et al, 2005Stelzer et al, , 2009 was evaluated in semen samples of falcons for the first time. Furthermore, eosin blue was compared in two different preparations (EB and EB2) to various established staining combinations of eosin yellow and eosin blue with different proportions of the background stains nigrosin or aniline (EYN5, EBN5 EYN10, EYA, EBA), respectively, to bromophenol blue-nigrosin (BBN) and the fluorescence stain SYBR ® Green-propidium iodide (SYBR-PI).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation